Self-Limiting and Self-Inflammatory Movements in Exchange Rates; Germany - Graham, Frank D. (Quarterly Journal of Economics, 1929)
I. Scope of the paper: certain self-inflammatory movements, indirect and provisional. — Three cases, distinguished according to the terms of sale, considered theoretically. Case I, 224. — Case II, 229. — Case III, 233. — Conditions in Germany during 1920–24 conform to the assumptions in these cases, 233. — II. Examination of German conditions, 236. — Two periods, 238. — Statistical verification for the two periods, 242. — Conclusion, 248.